Health Professions Educational Debt: Personal, Professional, and Psychological Impacts 5 Years Post-graduation - Webster, Patrick; North, Sara E. (Frontiers in Medicine, 2022)
Introduction: Cost burden in health professions education is rising. To bridge the gap between growing tuition and stagnating wages, student loans are increasingly obtained to cover educational costs. The spiraling after-effects are a source of acute concern, raising alarms across institutions and occupations. There is little dissemination to date of feasible data collection strategies and outcomes beyond one year post-graduation. Research is needed in evaluating the impacts of healthcare educational debt on career and personal choices following transition to practice. Materials and Methods: This study utilized a cross-sectional, mixed methods design. Doctor of Physical Therapy (DPT) Program graduates five years following degree completion completed a quantitative online survey, with topics including debt-to-income ratio, educational debt repayment strategies, impact on personal factors, non-education debt, and perceived value of their health professions education. Subsequent phone interviews were conducted by student researchers to gain insights into alumni perceptions of the impacts of educational debt on personal and professional decision-making. Data analysis involved descriptive and correlational quantitative statistics and open and axial coding of interview constructs. Results: The mixed methods format was successful in obtaining desired depth of response data. Quantitative findings demonstrated primary factors impacted by educational debt as savings, housing, leisure, discretionary spending, and family planning. Qualitative findings revealed impacts on themes of “personal factors” (81%), “professional factors” (62.5%), and “psychological factors” (56%) five years after graduation. Most negatively impacted were housing decisions, hours worked, initial job selection, and ability to save for the future, contributing to decreased mental health wellbeing with anxiety, frustration, and guilt. The majority (75%) of respondents perceived a high degree of value during and following their DPT education, though many expressed discordance between expectations and realities of practice. Discussion: Findings demonstrate that impacts of health professional educational debt in professional, personal, and psychological factors continue 5 years following degree completion, regardless of debt load. Successful implementation of this pilot methodology indicates potential for use of such extended data collection strategies. Further research is needed at the programs, profession, and/or interprofessional level to garner depth of understanding to guide interventions designed to mitigate or prevent these long-term repercussions.